Alkyd paint removal: Ionic liquid vs volatile organic compound (VOC) - Sarwono, A. (Elsevier B.V., 2018)
The drive towards safer technology in removing paint from substrate requires switching from hazardous volatile organic compounds to greener alternative solvents. Ionic liquids (ILs) have been considered as relatively green solvents and employed in many applications. This study focusses on investigation of ILs as alternative green solvents for paint removal. In this regard, five imdazolium based ILs were studied for alkyd paint removal on coated wooden substrate. The effect of various anions such as dicyanamide DCA, bis (trifluoromethanesulfonyl) imide NTf2, hydrogen sulphate HSO4, acetate OAc and chloride Cl was investigated. For benchmarking and comparison, three volatile organic solvents such as toluene, acetonitrile, and ethanol were used. Microscopic images showed that DCA anion gave significant impact on alkyd removal. In addition, BmimDCA gave highest swelling percentage of 23% whereas the other ILs did not show significant swelling. Viscosity, anion size and alkyd paint-IL interactions played important roles in removal efficacy. The prolonged immersion time in BmimDCA decreased the pull off adhesion strength up to 83.3% and consecutively promoted paint detachment from substrate. Similar infrared pattern of bare wooden stick and BmimDCA treated coated wooden stick indicates significant removal of paint by IL. The experimental results demonstrate promising application of IL as a green solvent for paint removal. Â© 2018 Elsevier B.V.